PEMBAHASAN MENGENAI LAPORAN KEUANGAN PERUSAHAAN DAGANG DI SMA TARSISIUS 1 JAKARTA - Jonathan, Michelle Leevia; Widyasari (Jurnal Bakti Masyarakat Indonesia, 2024)
Accounting is an important science to study. Considering that there are many high school students who have started small businesses, our PKM team carries out discussion activities regarding accounting material, one of which is regarding financial reports of trading companies. The aim of holding this lesson is for students to understand the basics of accounting, especially regarding financial reports. This material was discussed at Tarsisius I High School on Wednesday, for 90 minutes. This learning was carried out after we prepared the teaching materials that would be taught to students at Tarsisius 1 High School. The teaching materials we prepared were in the form of theory, example questions and quiz questions to find out how far the students understood about financial reports in trading companies. The lecturer explains the material for 10 to 15 minutes, and then our PKM Team continues with discussing example questions. The discussion of this example question is carried out with the aim that students who study financial reports can better understand the material we want to convey. After discussing the sample questions, we held a quiz with prizes at the end of our learning and also aimed to assess how well we understood and how influential our material discussion activities were on the students. The quiz lasts 10 to 15 minutes with a total of 10 questions via quizizz. The results we got after the quiz, students understood more about the financial reports of trading companies. So it can be concluded that the results of the discussion regarding the trading company's financial reports went well. ABSTRAK Ilmu akuntansi merupakan suatu ilmu yang penting untuk dipelajari. Mengingat banyaknya siswa/i Sekolah Menengah Atas yang sudah memulai bisnis kecil kecilan, maka tim PKM kami melakukan kegiatan pembahasan mengenai materi akuntansi, salah satunya mengenai laporan keuangan perusahaan dagang. Tujuan dari diadakannya pembelajaran ini adalah agar siswa/I memahami mengenai dasar-dasar akuntansi, terutama mengenai laporan keuangan. Pembahasan materi ini dilakukan di SMA Tarsisius I pada hari Rabu, selama 90 menit. Pembahasan materi dilakukan setelah kami mempersiapkan bahan ajar yang akan diajarkan kepada para pelajar di SMA Tarsisius 1. Bahan ajar yang kami siapkan berupa teori, contoh soal, dan soal kuis untuk mengetahui seberapa jauh siswa/i memahami tentang laporan keuangan di perusahaan dagang. Pemaparan materi dilakukan selama 10 hingga 15 menit oleh dosen, dan kemudian Tim PKM kami melanjutkan dengan pembahasan contoh soal. Pembahasan contoh soal ini dilaksanakan bertujuan agar siswa/i yang mempelajari mengenai laporan keuangan ini, dapat lebih paham mengenai materi yang ingin kami sampaikan. Setelah pembahasan contoh soal dilakukan, kami mengadakan kuis berhadiah sebagai akhir pembelajaran kami dan juga bertujuan untuk menilai seberapa paham dan seberapa berpengaruh kegiatan pembahasan materi kami terhadap siswa/i. Kuis berlangsung selama 10 hingga 15 menit dengan total 10 soal melalui quizizz. Hasil yang kami dapatkan setelah kuis, siswa/I lebih memahami tentang laporan keuangan perusahaan dagang. Sehingga dapat disimpulkan, hasil dari pembahasan mengenai laporan keuangan perusahaan dagang berjalan dengan baik.